Ecological effects of both single and combined pollution of Cd and bensulfuron-methyl on soil microorganisms - HU Zhu-bang; WANG Hai-zhen; WU Jian-jun; XU Jian-min (浙江大学学报. 农业与生命科学版)
The most important biological indicators characterizing the soil quality are soil microbial biomass carbon (Cmic), microbial biomass nitrogen (Nmic), soil basic respiration and soil phosphatase and sucrase activities. The dynamic effects of both single and combined pollution of Cd and bensulfuron-methyl herbicide on these biological indicators were studied under laboratory incubation conditions. Under the stress of both single and combined pollution of Cd and bensulfuron-methyl herbicide, the levels of these soil biological indicators were significantly reduced at the initial period, and then gradually increased with time. It was found that there was a significant interaction between Cd and ben-sulfuron-methyl herbicide in case of combined pollution. The toxicity effect followed the order of combined pollution of Cd and bensulfuron-methyl herbicide> bensulfuron-methyl herbicide>Cd.